Benang Merah Huffaz di Indonesia Studi Penelitian Biografi Huffaz - Khoeron, Mohamad (Lajnah Pentashihan Mushaf Al-Qur'an, 2011)
Over the past two years, the Committee for the Checking of the HolyÃ‚Â Qur'an (Lajnah Pentashihan Mushaf Al-QurÃ¢â‚¬â„¢an), Jakarta has carried out biographical research on huffaz (those who have learnt the QurÃ¢â‚¬â„¢an by the heart) in Indonesia. This article will attempt to draw out the key linkages from that research, and will also try to trace the role and position of the huffazÃ‚Â in preserving the traditions and the values of Islamic boarding schoolsÃ‚Â (pesantren). The experience of these guardians of the Qur'an as documented in this research reflects their persistence, patience and love for practising the teachings of the QurÃ¢â‚¬â„¢an, and it from these qualities thatÃ‚Â religious students andÃ‚Â huffazÃ‚Â emerge.Ã‚Â Their role in helpingÃ‚Â to educate the people of the nation is continuously being developed, based on a sincere determination to produce people with a Qur'anic orientation.